Gabay kawayan a study on the design of an inclusive playground equipment set that supports accessbility among Filipino children with reduced functions of lower extremities - Rodriguez, Abraham Borra
Play is one of the most important activities during childhood, thus providing such space that integrates play specifically for children must be considered as to something that is vital. However, not all children can utilize most preexisting play spaces that are installed within malls and public parks. Hence, a lot of Filipino children with disability could not access communal play structures where most children play. Project Gabay Kawayan, derived from the concept of bayanihan, aims to develop and provide such "barrier-free" avenues by designing a playground equipment set that adapts the concept of universality that will foster an inclusive bond that promotes communication and interaction amongst people of all ages and abilities which may elevate the participation of children with disability, in general the PWD within the community -- that will change the public perception of the value and practicality of incorporating accessible design and diversity into play spaces.